Combined mapping of DALP and AFLP markers in cultivated sunflower using F9 recombinant inbred lines - Langar, K; Lorieux, Mathias; Desmarais, E; Griveau, Y; Gentzbittel, I; Berville, A (2003)
A genetic map was constructed with specific PCRs, DALPs and AFLPs using F8-generation sunflower recombinant inbred lines. RI lines generated from a F2 population of one cross between the two cultivated inbred lines HA89 (maintainer for Pet1 CMS) and LR4 (restorer for Pet1 CMS) were used. A total of 305 markers were located using seven sPCR, 64 DALP and 301 AFLP loci. They were generated with one, seven and 14 primer pairs, respectively. The map construction consisted of a two-step strategy using 6 and 3.1 LOD scores revealed by a simulation file. Mapped markers were assembled into 18 linkage groups covering 2,168.6 cM with an average of 6.1 cM. The distribution of DALPs and AFLPs revealed that both markers tagged different regions to enable covering most of the sunflower genome. This leads to the longest map published so far for sunflower.